Exploring the coherence of urban heat adaptation plans - Tuomimaa, Julia; Käyhkö, Janina; Malmström, Alexandra; Juhola, Sirkku (Frontiers in Climate, 2026)
IntroductionAdaptation to heat is urgent given that the duration, frequency, and intensity of heat waves are increasing rapidly. However, there is a knowledge gap regarding the actions undertaken by cities in terms of heat adaptation and how coherent adaptation is across the stages of the policy cycle.MethodsBy conducting a policy document analysis we analyze how urban heat responses are linked to adaptation scope and beneficiaries and examine how different response types are monitored through indicators by exploring the adaptation policy cycle in four nodes: (i) scoping, (ii) defining measures, (iii) implementation, and (iv) monitoring and evaluation in 10 advanced cities located in heat-prone areas.ResultsOur analysis shows that most of our case cities plan adaptation to increase the population’s adaptive capacity, while the economic sector is prioritized less in adaptation measures. While the policy documents address in detail the implementation of actions; there is less clarity on indicator implementation and targeting of monitoring and evaluation.DiscussionThis study highlights the need for iterative, coherent adaptation policy planning and indicator utilization to enhance adaptation outcomes and guide future research and policy development.